Technological Applications of Biocatalysts - Open University (Biotechnologu by Open Learning (Series), 1993)
This work builds upon a knowledge of the properties of enzymes and shows how these important catalysts can be used in industry. The central theme demonstrates how proteins, especially enzymes and immunoglobins, can be isolated, characterized and produced on a large scale.